2014
DOI: 10.1159/000367588
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid and Cerebral Ischemia Risk: A Systematic Review of Observational Studies

Abstract: Background: Arachidonic acid (ARA) is a precursor of various lipid mediators. ARA metabolites such as thromboxane A2 cause platelet aggregation and vasoconstriction, thus may lead to atherosclerotic disease. It is unclear whether dietary ARA influences the ARA-derived lipid mediator balance and the risk for atherosclerotic diseases, such as cerebral ischemia. Considering the function of ARA in atherosclerosis, it is reasonable to focus on the atherothrombotic type of cerebral ischemia risk. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
3
6
0
Order By: Relevance
“…However, as in our cohort, this has not been observed in all studies (6,15,18) . Our results on the lack of association with AA, GLA and dihomo-γ-linolenic acid are consistent with other findings from other observational studies (6,14,17,19,21) . In the KIHD cohort, high hair Hg content was associated with a higher risk of CVD and with attenuation of the inverse association between n-3 PUFA and these events (22,23) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, as in our cohort, this has not been observed in all studies (6,15,18) . Our results on the lack of association with AA, GLA and dihomo-γ-linolenic acid are consistent with other findings from other observational studies (6,14,17,19,21) . In the KIHD cohort, high hair Hg content was associated with a higher risk of CVD and with attenuation of the inverse association between n-3 PUFA and these events (22,23) .…”
Section: Discussionsupporting
confidence: 93%
“…Circulating fatty acids provide an objective measure of exposure, and are thus less subject to random error. However, previous studies that have used circulating PUFA as exposure have not produced consistent findings (6)(7)(8)(14)(15)(16)(17)(18)(19)(20)(21) . Therefore, the aim of our study was to investigate the associations between serum n-3 and n-6 PUFA and risk of stroke in men.…”
mentioning
confidence: 85%
“…In addition, a more intensive synthesis of arachidonic acid (C20:4n6) was observed from essential fatty acids (EFAs), which probably includes linoleic acid (C18:2n6). These derivatives are responsible for the formation of blood clots, atherosclerotic changes, inflammatory and allergic reactions, cell proliferation, and the development of tumor tissue [21]. An increased percentage of C22:4n6 and omega-3-family acids, including C22:5n3 and C22:6n3 (EPA and DHA), were observed as well.…”
Section: Discussionmentioning
confidence: 99%
“…As for AA, this PUFA has complex biological functions, ranging from the participation in inflammation resolution mentioned above, to being a precursor of inflammatory mediators. The impact of AA on cardiovascular health and other inflammation-related disorders has not yet been conclusively established 62 . We showed that AA induces global DNA hypermethylation in human THP-1 monocytes (Silva-Martínez et al ., in press), in accordance with the positive association detected in the present study.…”
Section: Discussionmentioning
confidence: 99%